PELATIHAN KEPEMIMPINAN BIDANG KETRAMPILAN PUBLIC SPEAKING, SURVIVAL, CHARACTER BUILDING, DAN COMMUNITY BUILDING BAGI KEBIDELAN SEMINARI ST. PAULUS PALEMBANG - Vausta Nurjanah; M. K. Fitriani F.; Yohanes Heri Pranoto; Ig. Putra Setiahati; Anselmus Inharjanto (Universitas Muhammadiyah Mataram, 2020)
Abstrak: Tujuan dari kegiatan pelatihan kepemimpinan bidang ketrampilan Public Speaking, survival, Character Building, dan Community Buildingbagi kebidelan Seminari Menengah St. Paulus Palembang ini adalah meningkatkan kemampuan kepemimpinan siswa Seminari khususnya pengurus organisasi kesiswaan (kebidelan) dalam Public Speaking, survival, Character Building, dan Community Building. Metode yang dipakai berupa metode mimbar dan praktek dalam kelompok. Kegiatan berlangsung selama 3 hari dengan format camping sehingga ketrampilan survival, Character Building dan Community Building langsung dapat dipraktikkan. Materi dasar manajemen kepemimpinan dan Public Speaking ditempatkan pada hari kedua demi mendukung proses pelatihan dan dilaksanakan secara teoritis dan praktis. Dari hasil kuesioner pelaksanaan kegiatan, didapatkan respon yang positif (56%) dari seluruh peserta kegiatan menunjukkan signifikansi peningkatan skil peserta dalam kemampuan Public Speaking dan leadership.Abstract: The purpose of leadership training activities in the fields of Public Speaking, survival, Character Building, and Community Building skills for Midnight Seminary St. Paulus Palembang is to improve the leadership ability of Seminary students, especially the management of student organizations (kebidelan) in Public Speaking, survival, Character Building, and Community Building. The method used in the form of the pulpit method and practice in groups. The activity lasts for 3 days in a camping format so that survival, Character Building and Community Building skills can be put into practice immediately. The basic materials of leadership management and Public Speaking are placed on the second day to support the training process and are carried out theoretically and practically. From the results of the activity implementation questionnaire, positive responses (56%) were obtained from all participants shown the significancy skills improve on Public Speaking and leadership